Evidence for lymphatics in the developing and adult human choroid - Koina, M.; Baxter, L.; Adamson, S.; Arfuso, Frank; Hu, P.; Madigan, M.; Chan-Ling, T. (Association for Research in Vision and Ophthalmology Inc., 2015)
Purpose. Lymphatics subserve many important functions in the human body including maintenance of fluid homeostasis, immune surveillance, and tumor metastasis. Our aim was to provide structural and phenotypic evidence of lymphatic-like structures in the human choroid, including details of its development. Methods. Using multiple-marker immunohistochemistry (IHC), choroids from human fetal eyes (8–26 weeks gestation) and adults (17–74 years) were examined with lymphatic- and vascular-specific markers: prospero homeobox-1 (PROX-1), lymphatic vascular endothelium receptor-1 (LYVE-1), podoplanin, D2-40, endomucin, VEGF-C, vascular endothelial growth factor receptor-3 (VEGFR-3 or Flt4), UEA lectin, platelet endothelial cell adhesion molecule-1 (PECAM-1), CD34, and CD39. Transmission electron microscopy (TEM) was used to establish evidence for choroidal lymphatics, and to provide details of stratification and relative frequency of lymphatics compared to choroidal blood vessels. Results. Immunohistochemistry and TEM indicated a central-to-peripheral topography of lymphatic formation, with numerous blind-ended lymph sacs just external to the choriocapillaris, as well as the presence of infrequent precollector and collector lymphatic channels. Characteristic ultrastructural features of lymphatics in adult human choroid included anchoring filaments, luminal flocculent protein but absence of erythrocytes, fragmented and/or absent basal lamina, absence of intracellular Weibel-Palade bodies, infrequent pericyte ensheathment, and lack of fenestrae. Conclusions. The system of blind-ended initial lymphatic segments seen just external to the fenestrated vessels of the choriocapillaris is ideally placed for recirculating extracellular fluid and strategically placed for immune surveillance. The presence of a system of lymphatic-like channels in the human choroid provides an anatomical basis for antigen presentation in the posterior eye, with a possible route from the eye to the sentinel lymph nodes, similar to that already described for anterior eye lymphatics.